An insight into the draft genome of the Oriental rat flea, Xenopsylla cheopis, together with its Wolbachia endosymbiont - Stephen Lu; David M. Bland; Eric Dahlstrom; Neelam Redekar; Melina G. Guizzo; Kent Barbian; B. Joseph Hinnebusch; José M. C. Ribeiro (BMC Genomics)
Abstract Background The Oriental rat flea, Xenopsylla cheopis, is a main vector of plague caused by the bacterium Yersinia pestis. Transcriptomic analysis of this insect and the interaction between Yersinia and the flea digestive tract have been the subject of several studies. However, to develop more refined studies on this vector in the future, we sequence and describe a draft genome of the rat flea Xenopsylla cheopis, discuss the physiological implications of its genetic features, and compare them with the only other sequenced member of the Siphonaptera, the cat flea, Ctenocephalides felis. Results Sequencing data from both long and short reads were assembled into 7,694 contigs, from which 95,638 putative coding sequences (CDSs) were extracted and functionally annotated, providing insights into various aspects of flea physiology. This includes the identification of putative salivary proteins, such as acid phosphatases and FS-H/I, associated with blood acquisition; classification of multiple serine peptidases likely representing the primary digestive enzymes of X. cheopis; and the identification of all enzymes involved in heme biosynthesis, as well as heme oxygenases and unique heme-binding proteins potentially involved in heme detoxification. Comparison of detoxification-related genes—namely those in the cytochrome P450, carboxylesterase, and glutathione S-transferase families—with homologs from the cat flea (C. felis) revealed the presence of a platelet-activating factor (PAF) acetyl hydrolase that appears to be unique to rat fleas, cat fleas, and human head and body lice, but is absent in other blood-feeding arthropods. Additionally, we identified key components of immune-related pathways known from other arthropods, including the Toll, IMD, and JAK/STAT pathways. Finally, a contig encoding a novel bacterium was discovered within the assembled flea genome. Phylogenetic analysis of the Wolbachia endosymbiont in X. cheopis suggests it is closely related to the Wolbachia strain found in Drosophila melanogaster. Conclusions The disclosure of the X. cheopis genome, together with its Wolbachia symbiont, should advance research on the biology of this vector.